FACTOR ANALYSIS OF STUDENT PERCEPTION ON UNIVERSITAS ADVENT INDONESIA AS FAVORITE HIGHER EDUCATION INSTITUTION - Reymand M Hutabarat; Franklin Hutabarat (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This purpose of the study is to look on factors of in student perception on their reason whyUniversitas Advent Indonesia is their favorite higher education institution. By knowingthese factors could help the stakeholder of the university in their plan. A set of theinstrument of the questionnaire was acquired and distributed to 100 students respondent atUniversitas Advent Indonesia (UNAI). Exploratory factor analysis was used to distinguishthe underlying dimensions that drive student satisfaction. Factor analysis pertaining toanalysis on dimensions of Favorite University. The results show that the KMO test isvalued at 0.741 which is > 0.5; hence, the sample size is adequate for the analysis. On theother hand, the commonalities of all the variables are exceeding .4; consequently, all thevariables are useful in the model. The results show that factors in the analysis of studentsatisfaction on academic courses at UNAI are that the factor of student perception on UNAIas their favorite higher education institution is Facility and Quality of Education.